Expression Patterns of PACAP and PAC1R Genes and Anorexigenic Action of PACAP1 and PACAP2 in Zebrafish - Nakamachi, Tomoya; Tanigawa, Ayano; Konno, Norifumi; Shioda, Seiji; Matsuda, Kouhei (Frontiers in Endocrinology, 2019)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide which has potentiate to suppress the feeding behavior in rodent, chicken, and goldfish. Teleost fish has two PACAPs (PACAP1 coded by adcyap1a gene and PACAP2 coded by adcyap1b gene) and PACAP receptor, PAC1Rs (PAC1Ra coded by adcyap1r1a gene, and PAC1Rb coded by adcyap1r1b gene). However, expression pattern of two PACAP and PAC1R mRNA, and influence and relation of two PACAPs on feeding behavior in teleost fish is still unclear. Therefore we first examined the tissue and brain expression patterns of PACAP and PAC1R mRNAs. All PACAP and PAC1Rs mRNAs were dominantly expressed in the zebrafish brain. However, adcyap1a mRNA was also detected in gut and testis. In the brain, adcyap1b and adcyap1r1a mRNA level were greater than that of adcyap1a and adcyap1r1b respectively. adcyap1b and adcyap1r1a mRNA dominantly expressed in telencephalon and diencephalon. Highest level of adcyap1a mRNA was detected in the rhombencephalon and diencephalon, and of adcyap1r1b was detected in the cerebellum. In order to clarify the relationship between PACAP and feeding behaviour in the zebrafish, the effect of zebrafish (zf) PACAP1 or zfPACAP2 intracerebroventricular (ICV) injection on the food intake, and the change of PACAP mRNA levels on feeding status were examined. Food intake was significantly decreased by ICV injection of zfPACAP1 (2 pmol/g body weight), zfPACAP2 (2 or 20 pmol/g body weight) or mammalian PACAP (2 or 20 pmol/g). Meanwhile, all PACAP injection group did not changed the locomotor activity. By real-time PCR method, adcyap1 mRNA level was significantly increased at 2 and 3 hours after feeding compared with pre-feeding level, but adcyap1b, adcyap1r1a and adcyap1r1b mRNA level did not changed after feeding. These results suggest that expression level and distribution of duplicated PACAP and PAC1R genes are many differences in the zebrafish, and PACAP have anorexigenic effect in zebrafish as similar as other vertebrates.